2019
DOI: 10.1038/s41598-019-56358-2
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of liver fibrosis in children with obesity on two methods: transient and two dimensional shear wave elastography

Abstract: The aim of this study was to assess the liver stiffness values in children with obesity versus healthy children on 2D-SWE and TE taking into account different laboratory parameters. We performed a case-control study on 287 children aged between 3 to 18 years, admitted in a Romanian Pediatric Tertiary Hospital, which we divided according to the body mass index (BMI) into two groups: the study group-77 children with obesity, and control group-210 children with normal weight. All children underwent anamnesis, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
(48 reference statements)
2
26
1
Order By: Relevance
“…A potential advantage of elastographic measurement over liver biopsy is the ability to monitor liver disease progression (32). Recent studies have shown that shear wave elastography is an excellent method of assessing the degree of severity of liver fibrosis not only in adults but also in children and adolescents (23,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential advantage of elastographic measurement over liver biopsy is the ability to monitor liver disease progression (32). Recent studies have shown that shear wave elastography is an excellent method of assessing the degree of severity of liver fibrosis not only in adults but also in children and adolescents (23,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…TE is a non-imaging elastographic technique, while point shear wave elastography (p-SWE) and 2D-SWE combine imaging with elastography. The evidence currently suggests that p-SWE is as accurate as but more reliable than TE, while 2D-SWE is more accurate than TE (21)(22)(23). Some studies also speculated that the combination of TE and APRI could increase the accuracy of CFLD detection (12,24).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the methods for determining liver elasticity are: Transient Elastography (FibroScan), Sono-Elastography (Real-Time Tissue Elastography), Acoustic Radiation Force Impulse Elastography (ARFI), Supersonic Shear-Wave Elastography (2D-SWE) [52] and Magnetic Resonance Elastography (MRE). The techniques were also validated in the pediatric population and cut-off values have recently been published [53,54].…”
Section: Conventional Imaging Toolsmentioning
confidence: 99%
“…Improved data acquisition and computer interpretation will help remove human error in capsule endoscopy. All paediatric gastroenterology departments will have available to them fibroelastography 23 and hopefully all three variants of the same including ultrasound shear wave elastography 24 and magnetic resonance elastography, 25 although the latter two may depend on the largesse of radiology departments. These modalities will assess fibrosis and cirrhosis in patients with chronic liver disease and potentially fibrosis in other fibrosing diseases such as Crohn's disease and pancreatitis.…”
Section: Diagnosticsmentioning
confidence: 99%